CORPORATE GOVERNANCE DAN KINERJA KEUANGAN PERUSAHAAN (Studi pada Perusahaan Indonesia di Indeks LQ45 Tahun 2010-2014) - Halim Dedy Perdana; Rizzky Pradana Putra; Sri Murni (Jurnal Akuntansi, 2016)
Purpose - The purpose of this study was to examine the effect of corporate governance on the financial performance of the company. Corporate governance is measured using a proxy board size, independent board, and managerial ownership. While the company's financial performance is measured using the Return On Equity (ROE). Design / methodology / approach - The samples are companies included in the index LQ45 in 2010-2014 that have met the study criteria. The sample is determined by purposive sampling method with a total sample of 21 companies. This study uses multiple linear analyses to analyze influence of independent variables on the dependent variable. Findings - The results of this study indicate that the independent board has a positive influence on the financial performance of the company, while managerial ownership has a negative effect on the financial performance of the company. On the other hand, this study did not find any influence of board size on the financial performance of the company. Originality / value - This study examines whether the company's financial performance can be explained by determinants the same as those used in other similar studies. The results of the study indicate only independent board has positive effects on the company's financial performance. Keywords: corporate governance, ROE, financial firm performance